Nonlinear Radiative Treatment of Hydromagnetic Non-Newtonian Fluid Flow Induced by a Nonlinear Convective-Boundary-Driven Curved Sheet With Dissipations and Chemical Reaction Effects - Sanni, Kehinde Musodiq; Asghar, Saleem; Rashid, Saima; Chu, Yu-Ming (Frontiers in Physics, 2021)
The work investigates the flow of heat and mass transport of an incompressible MHD Cross fluid over a nonlinear curved stretching sheet. The energy equation incorporates viscous dissipation, radiative flux, and surface heating. The fluid concentration is distressed with chemical reaction whereas radially varying applied magnetic field is considered to examine the effects of Lorentz force and Ohmic heating. The fluid rheology is theoretically modelled and fundamentally novel for the completeness study of shear thinning and thickening fluids. Similarity method is utilized to reduce the governing system of PDE’s into ODE’s. Numerical computation through Runge-Kutta fourth order with shooting technique is implemented by first discretizing ODE’s into system of first order differential equations. The behaviors of the flow quantities; velocity, temperature, and concentration are graphically analyzed against the parameters including radius of curvature, fluid rheology, radiation, and reaction rate. The numerical results are validated in comparison with the published results. Studies on Newtonian fluids on flat and curved surfaces are the special cases of this work. The results are useful in material processing and polymer dynamics involving stretchable materials.